Advance care planning in the context of clinical deterioration: a systematic review of the literature. (January 2019) - Pearse, Wendy; Oprescu, Florin; Endacott, John; Goodman, Sarah; Hyde, Mervyn; O'Neill, Maureen
Background: A Rapid Response Team can respond to critically ill patients in hospital to prevent further deterioration and unexpected deaths. However, approximately one-third of reviews involve a patient approaching the end-of-life. It is not well understood whether patients have pre-existing advance care plans at the time of significant clinical deterioration requiring Rapid Response Team review. Nor is it understood whether such critical events prompt patients, their families and treating teams to discuss advance care planning and consider referral to specialist palliative care services. Aim and design: This systematic review examined advance care planning with patients who experience significant clinical deterioration in hospital and require Rapid Response Team review. The prevalence of pre-existing advance directives, whether this event prompts end-of-life discussions, the provision of broader advance care planning and referral to specialist palliative care services was examined. Data sources: Three electronic databases up to August 2017 were searched, and a manual review of article reference lists conducted. Quality of studies was appraised by the first and fourth authors. Results: Of the 324 articles identified through database searching, 31 met the inclusion criteria, generating data from 47, 850 patients. There was a low prevalence of resuscitation orders and formal advance directives prior to Rapid Response Team review, with subsequent increases in resuscitation and limitations of medical treatment orders, but not advance directives. There was high short- and long-term mortality following review, and low rates of palliative care referral. Conclusions: The failure of patients, their families and medical teams to engage in advance care planning may result in inappropriate Rapid Response Team review that is not in line with patient and family priorities and preferences. Earlier engagement in advance care planning may result in improved person-centred care and referral to specialist palliative care services for ongoing management.